Comprehensive approach to the problem of the effect of residual monomer on the immune-metabolic profile of patients with orthopedic treatment of non-removable temporary constructions - O. V. Voznyi; N. L. Khlystun; A. V. Dolia; P. L. Yushchenko; A. V. Yarova (Zaporozhye State Medical University, 2019)
The purpose of this work was to study the clinical effectiveness of the application of an advanced method of manufacturing temporary structures and its combination with the applications of hyaluronic acid and the internal administration of quercetin. Materials and methods. The subject of the study was the oral fluid, which was collected before preparation (stage I), 7 days after the establishment of the temporary structure (stage II), 14 days after the installation of permanent non-removable structure (stage III). In the oral fluid, the level of sIgA content and indicators of the state of oxidative homeostasis: reduced glutathione (RG), superoxide dismutase (SOD), catalase, urease and lysozyme were studied. The level of sIgA content was determined using the technique of immunoassay analysis using Vector-Best reagents. RG, SOD, catalase, urease and lysozyme have been investigated in biochemical spontaneous reactions, in accordance with the recommendations of existing methods. All patients were divided into 3 groups: I - control group, which used the standard methodology for the manufacture of temporary structures; ІІ - the main, for patients whose temporary structures were made according to an improved technique with evacuation; for the patients of the III (main) group temporary structures with the advanced technique and the parallel application of hyaluronic acid and quercetin were made. Results. Significant increase in the level of sIgA content was registered at the second stage - 7 days after the establishment of a temporary orthopedic construction (P < 0.05). At the same time, the reliable difference between the values of the indicators of I and II, I and III groups at the third stage was recorded - P ˂ 0.001. Significant differences in the level of activity of SOD in oral fluid were achieved between patients of groups I and III after the establishment of NOCs (respectively (1561.0 ± 36.0) с.u./min and (1442.0 ± 28.0) с.u./min, P < 0.05). At ІІ stage, the difference between the groups of comparison I and II by the level of catalase content was reliable at the level P < 0.05 - (6.54 ± 0.26) с.u./min and (5.3 ± 0.41) с.u./min, respectively, while the difference between I and III groups was reliable at P ˂ 0.01, the catalase index at the ІІ stage was(4.86 ± 0.48) с.u./min in the third group. At the third stage, in the It group, there was a further increase in the catalase to (8.64 ± 0.29) с.u./min, while the second and third group of patients had a significantly (P ˂ 0.001) better result - (5.33 ± 0.33) с.u./min and (4.48 ± 0.36) с.u./min, respectively. At the third stage of orthopedic treatment in the I group the lysozyme index is reduced to (39 ± 5) с.u./min, whereas in patients of group ІІ there is an increase in the result to (75 ± 6) с.u./min, and in ІІІ group it is completely stabilized, equaling (96 ± 4) c.u./min, P ˂ 0.01. Conclusions. Thus, by combining the use of the advanced prosthetic technique and the preparations of hyaluronic acid and quercetin, we have proved the effectiveness of this method and on the basis of the experimental and clinical results, we can safely assert that it is a complex approach to the problem of the effect of residual monomer on the immune-metabolic profile of patients with orthopedic treatment of non-removable temporary constructions to be the most effective.